2002
DOI: 10.1038/nn816
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and intentional brain responses during evaluation of trustworthiness of faces

Abstract: Successful social interaction partly depends on appraisal of others from their facial appearance. A critical aspect of this appraisal relates to whether we consider others to be trustworthy. We determined the neural basis for such trustworthiness judgments using event-related functional magnetic resonance imaging. Subjects viewed faces and assessed either trustworthiness or age. In a parametric factorial design, trustworthiness ratings were correlated with BOLD signal change to reveal task-independent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
704
5
13

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 882 publications
(795 citation statements)
references
References 46 publications
73
704
5
13
Order By: Relevance
“…Consistent with previous research, we found that post-task subjective trustworthiness ratings were influenced not only by the facial appearance of the partner (van 't Wout & Sanfey, 2008;Winston, Strange, O'Doherty, & Dolan, 2002), but also by the partner's behavior in the game (Delgado et al, 2005;Singer et al, 2004). Partners that reciprocated more frequently were rated as more trustworthy than partners that reciprocated infrequently.…”
Section: Subjective Ratings Of Trustsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous research, we found that post-task subjective trustworthiness ratings were influenced not only by the facial appearance of the partner (van 't Wout & Sanfey, 2008;Winston, Strange, O'Doherty, & Dolan, 2002), but also by the partner's behavior in the game (Delgado et al, 2005;Singer et al, 2004). Partners that reciprocated more frequently were rated as more trustworthy than partners that reciprocated infrequently.…”
Section: Subjective Ratings Of Trustsupporting
confidence: 88%
“…This study illustrates the conceptual and methodological advantages of an interdisciplinary approach and provides a novel quantitative framework to conceptualize the notion of trustworthiness as well as an approach to bridge the division between descriptive information and experienced information in the judgment and decision-making literature (Jessup et al, 2008). More broadly, our study provides an important and timely contribution to a growing literature interested in the neural computations underlying social learning (Behrens et al, 2008;Biele et al, 2009;Delgado et al, 2005;Hampton, Bossaerts, & O'Doherty, 2008;King-Casas et al, 2005;Olsson & Phelps, 2007) and trustworthiness (Krueger et al, 2007;Oosterhof & Todorov, 2008;van 't Wout & Sanfey, 2008;Winston, Strange, O'Doherty, & Dolan, 2002) and illustrates the importance of social beliefs in decision-making behavior.…”
Section: Resultsmentioning
confidence: 73%
“…On the functional level, the insula was found to be involved in the anticipation of electric shocks (Chua et al, 1999), noxious thermal stimuli (Ploghaus et al, 1999), fear indicating stimuli together with the amygdala (Phelps et al, 2001), and of aversive pictures (Simmons et al, 2004). Furthermore, the insula was found to be involved in differential positive versus negative emotion processing , particularly in fearful face processing , in pain perception (Peyron et al, 2000), in judgments about emotions (Gorno-Tempini et al, 2001), and, particularly the right anterior insula, in emotional states such as anger, disgust, sexual arousal, and subjective feeling of trustworthiness (Phillips et al, 1997;Stoleru et al, 1999;Winston et al, 2002). Accordingly, initial reports of the insula as being associated with disgust (Phillips et al, 1997) were modified towards concepts attributing a more general role in emotion processing (Paulus et al, 2005).…”
Section: Anatomical and Functional Features Of The Revealed Areasmentioning
confidence: 99%
“…Neurobiological models of social cognition posit that a network of neural structures is critically involved in processing social stimuli (Adolphs, 2001;Brothers, 1990;Phillips et al, 2003a). These models focus on regions of the occipital and temporal cortices such as the Fusiform Gyrus (FG) and Superior Temporal Sulcus (STS) which underlie face processing (Haxby, Hoffmann, & Gobbini, 2000;Winston, Henson, Fine-Goulden, & Dolan, 2004) and the amygdala which plays a critical role in detecting threat, recognizing emotions, and making complex social judgments (Adolphs et al, 1994;Adolphs et al, 1998;Amaral et al, 2003;Winston et al, 2002). Such models provide a foundation for understanding the neural mechanisms underlying social deficits in several clinical disorders, particularly schizophrenia and autism.…”
Section: Introductionmentioning
confidence: 99%